Assessment of 10-Year Left-Ventricular-Remodeling by CMR in Patients Following Aortic Valve Replacement - Rank, Nina; Stoiber, Lukas; Nasser, Mithal; Tanacli, Radu; Stehning, Christian; Knierim, Jan; Schoenrath, Felix; Pieske, Burkert; Falk, Volkmar; Kuehne, Titus; Meyer, Alexander; Kelle, Sebastian (Frontiers in Cardiovascular Medicine, 2021)
Aims: Aortic valve replacement (AVR) may result in reverse cardiac remodeling. We aimed to assess long-term changes in the myocardium following AVR by Cardiac Magnetic Resonance Imaging (CMR). Methods: We prospectively observed the long-term left ventricular (LV) function and structure of 27 patients with AVR (n = 19 with Aortic stenosis (AS); n = 8 with Aortic regurgitation (AR)) by CMR. Patients underwent CMR before, as well as 1, 5, and 10 years after AVR. We evaluated clinical parameters, LV volumes, mass, geometry, ejection fraction (EF), global myocardial longitudinal strain (MyoGLS), global myocardial circular strain (MyoGCS), hemodynamic forces (HemForces) and Late Gadolinium Enhancement (LGE). Results: The median of LVMI, EDVI, and ESVI decreased in both groups. Patients with AR had higher initial values of EDVI and ESVI and showed a more prominent initial reduction. In AS, MyoGLS improved already after one year and remained constant afterward, whereas in AR no improvement of MyoGLS was found. MyoGCS remained unchanged in the AS group but deteriorated in the AR group over 10 years. Ejection fraction (EF) was higher in AS patients compared to AR 10 years post AVR. Late gadolinium enhancement (LGE) could be found more frequently in AS patients. Conclusion: CMR was well suited to investigate myocardial changes over a 10-year follow up period in patients with aortic valve disease. Regarding the long-term functional changes following AVR, patients with AR seemed to benefit less from AVR compared to AS patients. Fibrosis was more common in AS, but this did not reflect functional evolution in these patients. Close monitoring seems indispensable to avoid irreversible structural damage of the heart and to perform AVR at an appropriate stage.